A lab equipped with industrial DCS for different control engineering courses. Issue 17 (2022) - Balke, Carina; Völtzer, Klaas; Dittmar, Rainer
Abstract: The paper describes the setup and operation of a control education lab which is used in different courses at both the undergraduate and graduate levels in electrical engineering and building systems programs. Its main characteristic is the equipment with several industrial-scale Distributed Control Systems (DCS) and the use of commercial software for its design and operation. Although procurement and maintenance costs are relatively high, the use of the lab across different study programs and courses results in high lab utilization and reasonable cost per individual lab. Some of the student projects are described in detail, among them the design of a DCS integrated Model Predictive Control (MPC) solution. The lab setup reduces the necessary system-specific training time for students and leads to a more efficient lab organization. Students appreciate the use of industry-related installation since it helps them to carry out a smooth transition from academia to industry.